Correlation between the GRACE Risk Score and the SYNTAX Score in Patients with Non-ST-Segment Elevation Myocardial Infarction - Huda, S M Nurul; Kabir, Mohammad Faisal Ibn; Haque, Mostashirul; Alam, Md Tasnim; Anwar, AFM Azim; Saha, Swadesh Kumar; Kabir, SK Md Nafis; Rahman, H N Ashiqur; Khaled, Md Fakhrul Islam; Parvin, Tanjima; Ahmed, Chaudhury Meshkat; Amin, Md Rasul (University Heart Journal, 2024)
Background: The GRACE risk score is a valid clinical tool to risk stratify patients with non-ST-segment elevation myocardial infarction (NSTEMI). The SYNTAX score is a comprehensive angiographic grading tool to determine the anatomic complexity of coronary artery disease. Predicting the SYNTAX score before a coronary angiogram (CAG) can help with patient counseling, optimization of planning, and preparation for possible complex percutaneous procedures or CABG in patients with NSTEMI. Objective: The objective of this study is to determine the correlation between the GRACE risk score and the SYNTAX score in patients with NSTEMI. Materials and Methods: A total of 52 patients with NSTEMI undergoing coronary angiography were enrolled in this study. According to the calculated GRACE score on admission, patients were divided into a low-risk group (GRACE score ≤108), an intermediate-risk group (GRACE score = 109–140), and a high-risk group (GRACE score > 140). After coronary angiography, the SYNTAX score was calculated. The correlation between the scores was determined by Pearson’s correlation test. Results: The mean SYNTAX score in the low GRACE risk group was 9.5 ± 5.1, in the intermediate GRACE risk group it was 12.5 ± 7.6, and in the high GRACE risk group it was 18.5 ± 8.9, and the differences were significant (P value = 0.005). There was a significant positive correlation (r = 0.515, p = <0.001) between the GRACE risk score and the SYNTAX score in patients with NSTEMI. Conclusion: Our study demonstrates that in NSTEMI patients, the GRACE risk score has a significant positive correlation with the SYNTAX score. University Heart Journal 2023; 19(2): 49-54